"Black skin – it's cheaper than rubber boots." Representations of colonialism in the travelogues of Jiří Hanzelka and Miroslav Zikmund - Chejnová, Anna (Dějiny – teorie – kritika, 2023)
The study deals with representations of colonialism in the travelogues by Jiří Hanzelka and Miroslav Zikmund. The main reason behind writing the text is the specific position of Czechoslovakia within the post-war colonial discourse and the fact that although Hanzelka a Zikmund are a famous pair of Czechoslovak travellers, such an analysis of their travelogues has not yet been carried out. The study aims to answer the question of how Hanzelka and Zikmund represented colonialism in their texts and what these representations say about them and the social environment from which they set out into the world. These representations are mostly associated with criticism of capitalism and were deployed to highlight the positive qualities of socialist regimes and to delineate the differences between the world of the so-called West and the world of the East. Today the label 'West' usually carries rather historically progressive connotations but Hanzelka and Zikmund tend to present quite the opposite, which creates an interesting difference between how they presented themselves outside their travelogues and what is recorded in their work. Indeed, the popularity of these authors in contemporary historical memory is linked, among other things, with their anti-communist attitudes and subsequent persecution (for example, the ban on publishing in their later years). The study also addresses the issue of the applicability of the concept of Orientalism to societies that were not direct participants in expansive colonial ventures.